A case report on digital preoperative design, clinical application and finite element analysis for a patient with ankylosing spondylitis kyphosis - Zhu, Lei; Zhang, Chi; Peng, Li; Cheng, Zifei; Liang, Xiuwen (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: By assessing a case of ankylosing spondylitis (AS) after thoracic lumbar protrusion deformity in a digital model and verifying its effectiveness after surgery for orthopaedic surgery process simulation, a finite element model was established for biomechanical experiments. Method: A 56-year-old patient with AS underwent preoperative thoracic lumbar spine computed tomography. The data were reconstructed using MIMICS16.0 software and modelled to design and measure the nailing parameters. A three-dimensional model was established using ANSYS14.0 software, and the actual surgical procedure was simulated using biomechanical experiments. The model was verified by comparing the X-ray films obtained from patients during preoperative forward bending, stretching and lateral flexion, with the model further tested using the Hueter–Volkmann principle. Result: On comparing the measurements across three different load cases (forward bending, after stretching and lateral flexion) in patients with AS after thoracic lumbar protrusion deformity and the original X-ray images, no difference was found between the model of deformation and real patient movement displacement across the vertebral body. On simulating the stress distribution, the measured T10–L4 vertebral body stress values at every point in the injured vertebrae were, on the whole, directed at both the upper and lower ends and exhibited a decreasing trend, and the stress distribution gradually decreased from the injured vertebrae (T12 and L1) to the upper and lower ends. Conclusion: The accuracy of the research model is high, the geometric similarity is good and relevant applied anatomy can be undertaken using the model parameter measurement. This study provides a successful example of the application of digital technology in the field of spinal deformity and a novel idea for the treatment of AS-related kyphosis.